KREATIVITAS SISWA DALAM PEMBELAJARAN DENGAN MODEL PEMBELAJARAN BERDIFERENSIASI - Rahmayani, Ida; Salam, Agus; Kusumawati, Yayuk (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
With the diversity of learning styles that each student has in the classroom, the teacher must choose a learning strategy that is in accordance with the development of the student's learning process. The application of differentiated learning strategies is the right alternative to balance and increase student enthusiasm in learning and meet the varied learning needs of students. This research examines student creativity in differentiated learning in grade V SDIT Insan Kamil Kota Bima by involving content, process and product adjustments in individual student differences. This research uses qualitative methods with a descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that differentiated learning enhances creativity by providing space for students to learn according to their learning styles and needs. Students show increased motivation and ability to think creatively in an environment that supports their interests and talents. as for the factors that affect student creativity 1.) lack of creative student interest 2.) lack of talent in digital utilization (canva) 3.) limited time. These findings emphasize the importance of differentiated learning models to develop students' creativity potential